Properties of Reclaimed Asphalt Pavement (RAP) Stabilized with Crushed Rock and Stone Dust - Khan-ngern, Khemaporn; Jaritngam, Saravut; Somchainuek, Opas (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2026)
This research investigated the properties of reclaimed asphalt pavement (RAP) stabilized with crushed rock and stone dust for use as an alternative pavement material. Crushed rock and stone dust were employed as stabilizing additives to enhance the compressive strength of RAP. Both additives were first subjected to gradation analysis, and materials meeting the specification were selected for mix design. Pavement in-place recycling mixtures were designed in accordance with the Thai Department of Highways standard DH-S 213/2543 for reclaimed asphalt pavement (RAP). The mixtures were prepared by combining RAP with two types of additives crushed rock and stone dust at three RAP-to-additive ratios of 25:75, 50:50, and 75:25 by weight. Unconfined compressive strength tests were conducted on the prepared mixtures. The results indicated that stabilized RAP has potential for use as an alternative material in road construction and rehabilitation. In particular, the mixture with a RAP-to-additive ratio of 25:75 satisfied the Department of Highways requirement for a cement-treated gravel subbase layer, achieving a minimum unconfined compressive strength of 24.50 kgf/cm2 (ksc) after 7 days of curing.